Longitudinal imaging of individual olfactory sensory neurons in situ - Zak, Joseph D. (Frontiers in Cellular Neuroscience, 2022)
Olfactory sensory neurons are found deep within the nasal cavity at a spatially restricted sheet of sensory epithelium. Due to their location behind the nasal turbinates, accessing these cells for physiological measurements in living animals is challenging, and until recently, not possible. As a further complication, damage to the overlying bone on the dorsal surface of the snout disrupts the negative pressure distribution throughout the nasal cavities, which fundamentally alters how odorants are delivered to the sensory epithelium and the inherent mechanosensory properties of olfactory sensory neurons in live animals. We have devised an approach that circumvents these limitations and allows for optical access to olfactory sensory neurons in mice across time scales ranging from days to months.